Demilitarizing politics : elections on the uncertain road to peace - Lyons, Terrence (Lynne Rienner Publishers, 2005)
Asking why some postconflict elections succeed and others fail, Lyons finds the answer in the internal political dynamics that occur between the cease-fire and the voting.